2023
DOI: 10.3389/fpubh.2022.1026236
|View full text |Cite
|
Sign up to set email alerts
|

Completion of the continuum of maternity care and associated factors among women who gave birth in the last 6 months in Chelia district, West Shoa zone, Ethiopia: A community-based cross-sectional study

Abstract: BackgroundThe continuum of maternity care is a continuity of care that a woman receives during pregnancy, childbirth, and the postpartum period from skilled providers in a comprehensive and integrated manner. Despite existing evidence regarding maternal healthcare services discretely, the continuum of maternity care and its associated factors are not well-known in Ethiopia.ObjectiveThis study assessed the completion of the maternity continuum of care and associated factors among women who gave birth 6 months p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…For instance, a study by Alemi et al ( 3 ) established that accompanying a pregnant woman to antenatal care raised the odds of commencing antenatal visits during the first trimester, adequate use of antenatal care services, health facility delivery and presenting for postnatal check-ups. Reports from numerous studies similarly indicated that male participation in pregnancy-related care predicted increased likelihoods of maternal health service utilization, continuum of care completion, infectious diseases prevention, obstetric complications awareness, birth preparedness involvement, reduction in postpartum depression and postpartum modern contraception utilization ( 5 , 6 , 26 , 28 , 30 32 ). Thus, active male partner's support during pregnancy can enhance the quality of life of mother and child and facilitate reduction in the rates of maternal and child morbidity and mortality in low- and middle-income countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a study by Alemi et al ( 3 ) established that accompanying a pregnant woman to antenatal care raised the odds of commencing antenatal visits during the first trimester, adequate use of antenatal care services, health facility delivery and presenting for postnatal check-ups. Reports from numerous studies similarly indicated that male participation in pregnancy-related care predicted increased likelihoods of maternal health service utilization, continuum of care completion, infectious diseases prevention, obstetric complications awareness, birth preparedness involvement, reduction in postpartum depression and postpartum modern contraception utilization ( 5 , 6 , 26 , 28 , 30 32 ). Thus, active male partner's support during pregnancy can enhance the quality of life of mother and child and facilitate reduction in the rates of maternal and child morbidity and mortality in low- and middle-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…Education is the most consistent social determinant health of a society as it informs knowledge, attitude and practice that promotes positive health behaviors and outcomes ( 35 ). This is evidenced by numerous studies addressing various public health issues including pregnancy-related care ( 7 , 23 , 25 , 30 , 33 , 35 , 36 ). Education substitutes traditional gender norms with liberal attitudes of shared responsibility, provides access to resources and equips individuals with relevant knowledge across various life domains, including reproductive health, thus, fostering increased male partner's engagement during pregnancy ( 12 , 37 ).…”
Section: Discussionmentioning
confidence: 99%